Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2340/00015555-3485
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Rhinitis and Asthma Among Adolescents with Psoriasis: A Population-based Cross-sectional Study

Abstract: In a population-based cross-sectional study among adolescents, psoriasis was shown to be significantly associated with allergic rhinitis and asthma. The association between psoriasis and asthma was found only in moderate-to-severe psoriasis, while the association with allergic rhinitis was not dependent on psoriasis severity. Few studies have reported an association between psoriasis and atopic comorbidity in adults.A population-based cross-sectional study was performed to investigate the possible association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…A previous study showed that RAST was positive in 58 and 22% of patients with chronic plaque psoriasis and active psoriasis, respectively ( 79 ). Several studies showed similar results, in which the positive RAST tests were significantly higher in patients with chronic plaque psoriasis(CPP) than those with progressive psoriasis ( 50 , 80 ). However, contradictory results have also been reported.…”
Section: Potential Association Between Psoriasis and Igementioning
confidence: 71%
“…A previous study showed that RAST was positive in 58 and 22% of patients with chronic plaque psoriasis and active psoriasis, respectively ( 79 ). Several studies showed similar results, in which the positive RAST tests were significantly higher in patients with chronic plaque psoriasis(CPP) than those with progressive psoriasis ( 50 , 80 ). However, contradictory results have also been reported.…”
Section: Potential Association Between Psoriasis and Igementioning
confidence: 71%
“…Alerjik rinit ve bronşiyal astım birlikteliği sık görüldüğü bildirilmiştir (11,12). Çalışmamızda da literatürle uyumlu olarak çalışma grubunun yaklaşık yarısında bu iki alerjik hastalığın birlikteliği görülmüştür.…”
Section: Discussionunclassified
“…Older patients with psoriasis (≥50 years) had a higher risk of asthma (OR = 1.64, 95% CI: 1.44-1.88) and chronic obstructive pulmonary disease (HR = 2.19, 95% CI: 1.27-3.77) than younger ones [12,23]. In children, observational studies suggest an increased risk of asthma compared to the general population, but the data are inconsistent [13,[17][18][19]. Furthermore, the increased susceptibility to asthma in children was associated with moderate to severe psoriasis [17].…”
Section: Prevalence Of Lung Diseases In Psoriasismentioning
confidence: 99%
“…In children, observational studies suggest an increased risk of asthma compared to the general population, but the data are inconsistent [13,[17][18][19]. Furthermore, the increased susceptibility to asthma in children was associated with moderate to severe psoriasis [17].…”
Section: Prevalence Of Lung Diseases In Psoriasismentioning
confidence: 99%